Xenoantibodies to porcine non-galactose α1, 3 galactose antigens in non-human primates cross-react and cause apoptosis to human endothelial cells. Issue 5 (2015) - Mañez, Rafael; Moscoso, Isabel; Costa, Cristina; Centeno, Alberto; Lopez-Pelaez, Eduardo; Suarez, Natalia; Domenech, Nieves
No abstract available